Longitudinal development of match-running performance in elite male youth soccer players - Saward, C.; Morris, J. G.; Nevill, M. E.; Nevill, A. M.; Sunderland, C. (Scandinavian Journal of Medicine & Science in Sports, 2016)
This study longitudinally examined age-related changes in the match-running performance of retained and released elite youth soccer players aged 8-18 years. The effect of playing position on age-related changes was also considered. Across three seasons, 263 elite youth soccer players were assessed in 1-29 competitive matches (988 player-matches). For each player-match, total distance and distances covered at age group-specific speed zones (low-speed, high-speed, sprinting) were calculated using 1 Hz or 5 Hz GPS. Mixed modeling predicted that match-running performance developed nonlinearly, with age-related changes best described with quadratic age terms. Modeling predicted that playing position significantly modified age-related changes (P < 0.05) and retained players covered significantly more low-speed distance compared with released players (P < 0.05), by 75 ± 71 m/h (mean ± 95% CI; effect size?±?95% CI: 0.35 ± 0.34). Model intercepts randomly varied, indicating differences between players in match-running performance unexplained by age, playing position or status. These findings may assist experts in developing training programs specific to the match play demands of players of different ages and playing positions. Although retained players covered more low-speed distance than released players, further study of the actions comprising low-speed distance during match play is warranted to better understand factors differentiating retained and released players.